Respuesta :
A number (x) minus 25 (-25) is equal to (=) 51 (51).
Rewrite everything only in parenthesis.
x - 25 = 51
Now, we can solve.
To solve for x, we need for it to be on one side by itself. However, x is subtrating 25. To get rid of -25, we must perform the opposite order of operations.
Remember, what you do to one side of an equation, you must do to the other.
Add 25 to both sides.
-25 + 25 = 0
51 + 25 = 76.
We are now left with:
x = 76.
I hope this helps!
Rewrite everything only in parenthesis.
x - 25 = 51
Now, we can solve.
To solve for x, we need for it to be on one side by itself. However, x is subtrating 25. To get rid of -25, we must perform the opposite order of operations.
Remember, what you do to one side of an equation, you must do to the other.
Add 25 to both sides.
-25 + 25 = 0
51 + 25 = 76.
We are now left with:
x = 76.
I hope this helps!
x − 25 = 51 .
This is the expression that would be written; in which "x" refers to the particular number.
To solve for that number, one would add 25 to EACH SIDE of the equation; to isolate "x" (the particular number to be solved for) on ONE SIDE of the equation; and to solve for "x" (that particular number) ; AS FOLLOWS:
_________________________________
x − 25 = 51 ;
Add 25 to each side of the equation;
x − 25 + 25 = 51 + 25 ;
to get:
x = 76.
____________________________________________
The particular number is: " 76 " .
____________________________________________
This is the expression that would be written; in which "x" refers to the particular number.
To solve for that number, one would add 25 to EACH SIDE of the equation; to isolate "x" (the particular number to be solved for) on ONE SIDE of the equation; and to solve for "x" (that particular number) ; AS FOLLOWS:
_________________________________
x − 25 = 51 ;
Add 25 to each side of the equation;
x − 25 + 25 = 51 + 25 ;
to get:
x = 76.
____________________________________________
The particular number is: " 76 " .
____________________________________________